Analysis of the Implementation of Business-To-Business (B2B) Marketing Strategy in Client Acquisition Efforts at PT Talenta Sinergi Group - Fikri Firmansyah; Ratna Roostika; Fahmi Maulana (Journal Research of Social Science, Economics, and Management, 2026)
The development of digital transformation has increased the demand for talent in the technology field, leading to stronger competition among talent service providers and the need for more targeted marketing strategies. This research aims to analyze Business-to-Business (B2B) marketing strategies at Upscale, focusing on the application of Segmenting, Targeting, Positioning (STP), Marketing Mix (4P), and email marketing as the main promotional channel. This study employs a qualitative approach, with data collected through interviews, observations, and documentation during the internship period at Upscale. The results show that the STP strategy is implemented by segmenting the market based on recruitment activities on online portals to target credible companies in need of technology talent, while positioning Upscale as an integrated service provider. The marketing mix is executed through talent solution and infrastructure setup offerings, flexible pricing based on project complexity, service distribution without geographical limitations, and digital promotion primarily relying on email marketing. The email marketing strategy is carried out through stages of identification, verification, and the delivery of personalized mass messages; however, its implementation is still constrained by the quality of contact data and the high volume of promotional emails.